Clinicopathologic subtype of Alzheimer's disease presenting as corticobasal syndrome. Issue 9 (6th August 2019) - Sakae, Nobutaka; Josephs, Keith A.; Litvan, Irene; Murray, Melissa E.; Duara, Ranjan; Uitti, Ryan J.; Wszolek, Zbigniew K.; van Gerpen, Jay; Graff‐Radford, Neil R.; Dickson, Dennis W.
Abstract: Introduction: The corticobasal syndrome (CBS) is associated with several neuropathologic disorders, including corticobasal degeneration and Alzheimer's disease (AD). Method: In this report, we studied 43 AD patients with CBS (AD‐CBS) and compared them with 42 AD patients with typical amnestic syndrome (AD‐AS), as well as 15 cases of corticobasal degeneration and CBS pathology. Results: Unlike AD‐AS, AD‐CBS had prominent motor problems, including limb apraxia (90%), myoclonus (81%), and gait disorders (70%). Alien limb phenomenon was reported in 26% and cortical sensory loss in 14%. Language problems were also more frequent in AD‐CBS, and memory impairment was less frequent. AD‐CBS had more tau pathology in perirolandic cortices but less in superior temporal cortex than AD‐AS. In addition, AD‐CBS had greater neuronal loss in the substantia nigra. Discussion: AD‐CBS is a clinicopathological subtype of AD with an atypical distribution of Alzheimer‐type tau pathology. Greater neuronal loss in the substantia nigra may contribute to Parkinsonism which is not a feature of typical AD.